Estimating the Precision of the Likelihood-Ratio Output of a Forensic-Voice-Comparison System - Morrison, G.S.; Thiruvaran, T.; Epps, J. (My University, 2010)
The issues of validity and reliability are important in forensic science. Within the likelihood-ratio framework for the evaluation of forensic evidence, the log-likelihood-ratio cost (Cllr) has been applied as an appropriate metric for evaluating the accuracy of the output of a forensic-voice-comparison system, but there has been little research on developing a quantitative metric of precision. The present paper describes two procedures for estimating the precision of the output of a forensic-comparison system, a non-parametric estimate and a parametric estimate of its 95% credible interval. The procedures are applied to estimate the precision of a basic automatic forensic-voice-comparison system presented with different amounts of questioned-speaker data. The importance of considering precision is discussed.